Principles of Cancer Genetics - Bunz, Fred.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Cancer genetics is a field of daunting breadth and depth. The literature describes hundreds of genes and genetic alterations that are variably associated with again as many disease states and risk factors. Integrating these disparate pieces of highly specialized information is challenging for the professional scientist and student alike. Prinicples of Cancer Genetics consolidates the main concepts of the cancer gene theory, and provides a framework for understanding the genetic basis of cancer. Focused on the most highly representative genes that underlie the most common cancers, Principles of Cancer Genetics is aimed at advanced undergraduates who have completed introductory courses in genetics, biology and biochemistry, medical students, and house medical house staff preparing for board examinations. Primary attention is devoted to the origins of cancer genes and the application of evolutionary theory to explain why the cell clones that harbor cancer genes tend to expand. The many points of controversy in cancer research are avoided, in favor of firmly established concepts. This book does not delve into tumor pathobiology beyond what is required to understand the role of genetic alterations in neoplastic growth. For students with a general interest in cancer, this book will provide a highly accessible overview. For students contemplating future study in the fields of oncology or cancer research, this book will be useful as a primer.
The Genetic Basis of Cancer -- Oncogenes -- Tumor Suppressor Genes -- Genetic Instability and Cancer -- Cancer Gene Pathways -- Genetic Alternations in Common Cancers -- Cancer Genetics in the Clinic.
Keywords: MEDICINE; ONCOLOGY; HUMAN GENETICS; BIOMEDICINE; CANCER RESEARCH; ONCOLOGY; HUMAN GENETICS; BIOMEDICINE GENERAL